2019
DOI: 10.1038/s41467-019-09951-y
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of echolocation and dietary ecology in the adaptive evolution of skull shape in bats

Abstract: Morphological diversity may arise rapidly as a result of adaptation to novel ecological opportunities, but early bursts of trait evolution are rarely observed. Rather, models of discrete shifts between adaptive zones may better explain macroevolutionary dynamics across radiations. To investigate which of these processes underlie exceptional levels of morphological diversity during ecological diversification, we use modern phylogenetic tools and 3D geometric morphometric datasets to examine adaptive zone shifts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(135 citation statements)
references
References 75 publications
10
125
0
Order By: Relevance
“…The main dimension of phyllostomid cranial evolution is the length of the skull and snout, a morphological characteristic important to phyllostomid feeding ecology [5,10,15,54]. The faces of phyllostomids show a full range of phenotypes from the extremely shortened-faces of the fruit bats to the highly elongated faces of the nectarfeeding bats, which encompass the majority of variation based on principal components (PC) analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The main dimension of phyllostomid cranial evolution is the length of the skull and snout, a morphological characteristic important to phyllostomid feeding ecology [5,10,15,54]. The faces of phyllostomids show a full range of phenotypes from the extremely shortened-faces of the fruit bats to the highly elongated faces of the nectarfeeding bats, which encompass the majority of variation based on principal components (PC) analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In concert with ecological diversification, noctilionoids evolved highly diverse sensory modalities, including infrared thermal radiation detection in vampire bats, high duty cycle (HDC) echolocation in the Pteronotus parnellii species complex (family Mormoopidae), and inferred ultraviolet (UV) perception in some nectar‐feeding lineages (Gracheva et al., 2011; Smotherman & Guillen‐Servent, 2008; Winter, Lopez, & Helversen, 2003). However, most previous research has focused on the relationship between noctilionoid diet and morphology (Arbour, Curtis, & Santana, 2019; Dumont et al., 2012; Rojas et al., 2011), with analyses linking foraging modes and molecular adaptations of sensory systems in this clade having only recently started (Hayden et al., 2014; Hong & Zhao, 2014; Sadier et al., 2018; Yohe et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These observations may have two explanations. Arbour et al [78] found that echolocation related to an early lineage of species had a greater contribution than diet to the evolution of the cranium in bats. Moreover, the skull morphology in carnivores and marsupials are strongly influenced by phylogeny, especially in felids, ursids, and canids [26,79,80].…”
Section: The Relationship Between Skull Morphology With Bite Force Anmentioning
confidence: 99%